Immediate improvement in coronary flow reserve after alcohol septal ablation in patients with hypertrophic obstructive cardiomyopathy. Issue 7 (24th October 2008) - Jaber, W A; Yang, E H; Nishimura, R A; Sorajja, P; Rihal, C S; Elesber, A; Eeckhout, E; Lerman, A
Abstract : Objectives: To examine whether percutaneous alcohol septal ablation affects coronary flow reserve (CFR) in patients with hypertrophic cardiomyopathy (HCM). Methods: CFR was measured immediately before and after septal ablation in patients with symptomatic obstructive HCM. CFR was also obtained in normal subjects (NL) for comparison. Results: Patients with HCM (n = 11), compared with NL (n = 22), had a lower mean (SD) baseline CFR (1.96 (0.5) vs 3.0 (0.7), p<0.001), a lower coronary resistance (1.04 (0.45) vs 3.0 (2.6), p = 0.002), a higher coronary diastolic/systolic velocity ratio (DSVR; 5.1 (3.0) vs 1.8 (0.5), p = 0.04) and a lower hyperaemic coronary flow per left ventricular (LV) mass (0.73 (0.4) vs 1.1 (0.6) ml/min/g, p = 0.007). Septal ablation in the HCM group (n = 7) reduced the outflow tract gradient but not the left atrial or LV diastolic pressures. Ablation resulted in immediate normalisation of CFR (to 3.1 (1), p = 0.01) and DSVR (to 1.9 (0.8), p = 0.09) and an increase in coronary resistance (to 1.91 (0.6), p = 0.02). This was probably related to an improvement in the systolic coronary flow. Conclusions: This study demonstrates that successful septal ablation in patients with symptomatic HCM results in immediate improvement in CFR, which is reduced in HCM partly because of the increased systolic contraction load.